Respostas
respondido por:
2
a) 3x²-21x= x²-5
3x²-x²-21x+5=0
2x²-21x+5=0
b) 4x²+5x= 3x²+6x -x-3
x²-x+x+3
x²+3=0
c) x²+4x+4=x+4
x²+3x=0
3x²-x²-21x+5=0
2x²-21x+5=0
b) 4x²+5x= 3x²+6x -x-3
x²-x+x+3
x²+3=0
c) x²+4x+4=x+4
x²+3x=0
elizangelaparec:
agradecida pela ajuda
respondido por:
1
Boa tarde
a)
3x*(x - 7) = x² - 5
3x² - 21x = x² - 5
2x² - 21x + 5 = 0
b)
5x + 4x² = 3x*(x + 2) - x - 3
5x + 4x² = 3x² + 6x - x - 3
x² + 3 = 0
c)
(x + 2)² = x + 4
x² + 4x + 4 = x + 4
x² + 3x = 0
a)
3x*(x - 7) = x² - 5
3x² - 21x = x² - 5
2x² - 21x + 5 = 0
b)
5x + 4x² = 3x*(x + 2) - x - 3
5x + 4x² = 3x² + 6x - x - 3
x² + 3 = 0
c)
(x + 2)² = x + 4
x² + 4x + 4 = x + 4
x² + 3x = 0
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás